Clinicoepidemiological Profile of Otorhinolaryngological Diseases among Patients Aged 5-15 Years- A Retrospective Study - Mohan Kumar Mili; Asha Saikia; Monikuntal Sarmah; Jyotirmoy Phookan; Naba Jyoti Saikia (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Ear, nose and throat diseases are some of the common causes of absenteeism among the school going children and can contribute to various co-morbidities. The most common among the Ear, Nose, Throat (ENT) diseases in school going children is hearing impairment due to ear wax or different types of otitis media which can be prevented with early detection and intervention. Upper respiratory tract infections also predispose a child to complications such as tonsillitis, sinusitis along with otitis media that can lead to morbidities like hearing impairment and learning disability. Aim: To determine the prevalence of ear, nose and throat diseases among the school going children and their clinico-epidemiological profile. Materials and Methods: This retrospective study was carried out in a tertiary care centre, Assam Medical College and Hospital, Dibrugarh, Upper Assam, India during the period of January 2019 to December 2019. Study included all the 1525 children within age group of 5-15 years attending the ENT Outpatient Department (OPD). Data was obtained from the outdoor register and the history sheets. Data collected was age, sex, religion and distribution of diseases according to site. Number of children having ear, nose, throat or neck diseases were calculated using Microsoft Excel software 2013, version 15.0. Results: Majority of the cases studied were found to be in the age group of 5-10 years (54.1%). ENT diseases were more common in boys (54.2%) than in girls (45.8%). Diseases of the ear (55.9%) were most common, followed by oral cavity and throat (19.3%), nose and Paranasal Sinus (PNS) (18.2%) and neck (6.6%). The most common diseases in ear were Chronic Suppurative Otitis Media (CSOM) and presence of earwax, while sinusitis and allergic rhinitis were more prevalent in diseases of nose and PNS. Pharyngitis and tonsillitis were more commonly found among the diseases of oral cavity and throat. Conclusion: These diseases are a major burden in the school going children resulting in their absence from school, low academic and extracurricular performance and other outdoor activities. Keeping an eye on this aspect, a structured and systematic school health program can be designed in collaboration with state health system, so that it can be properly followed-up and needed treatment can be initiated with the help of state government cost.